2021
DOI: 10.1088/2053-1583/ac2245
|View full text |Cite
|
Sign up to set email alerts
|

2-dimensional polar metals: a low-frequency Raman scattering study

Abstract: The intercalation of a molecule or ion in a layered structure is key to enhancing energy storage, material conductivity, intercalant structural ordering, and the formation of two-dimensional (2D) superconducting states. The process of intercalation modifies the vibrational energy of the host, which can be monitored non-invasively by Raman spectroscopy. However, the detected Raman spectral shifts may originate from a variety of phenomena, generally making the technique an indirect means of identifying intercala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…The atomic structure of 2D Ga on SiC used in this work (e.g., Figure a) is consistent with high-resolution high-angle annular dark-field cross-sectional scanning transmission electron microscope (HAADF-STEM) images (Figure S1) and represents the energetically most stable structure according to density functional theory (DFT) calculations . Experimentally, it has been found that the low-frequency Raman spectra are independent of the number of graphene overlayers on top of 2D Ga . Our DFT calculations also show that the graphene shear and breathing modes are essentially decoupled from the Ga and SiC phonons (Table S1).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…The atomic structure of 2D Ga on SiC used in this work (e.g., Figure a) is consistent with high-resolution high-angle annular dark-field cross-sectional scanning transmission electron microscope (HAADF-STEM) images (Figure S1) and represents the energetically most stable structure according to density functional theory (DFT) calculations . Experimentally, it has been found that the low-frequency Raman spectra are independent of the number of graphene overlayers on top of 2D Ga . Our DFT calculations also show that the graphene shear and breathing modes are essentially decoupled from the Ga and SiC phonons (Table S1).…”
supporting
confidence: 84%
“…This observation is distinct from that in van der Waals layered materials, and arises from the coupling of the 2D metal to the substrate, which results in an asymmetric bonding profile in the system. We expect that the low-frequency shear modes predicted here will also be present in other 2D metals (e.g., In, Ag, alloys) that have similarly been fabricated by heteroepitaxy on SiC. A clear understanding of the low-frequency phonon modes in these 2D polar metals is important for developing an atomic-scale understanding of the coherent, coupled electron and phonon dynamics in these emerging systems …”
mentioning
confidence: 58%
“…The deterministic stacking order and interlayer twist angles provide highly tunable electronic properties, which are especially demonstrated by the realization of superconducting phases in twisted bilayer graphene. On the other hand, bottom-up growth provides an alternative for high quality and stability over wafer-scale lengths, with a particular interest in epitaxial graphene layers obtained by thermal decomposition of silicon carbide (0001) substrates. ,, In this case, the intercalation of heteroatoms under graphene layers is the most promising strategy for the synthesis of designer 2D materials . First, intercalation was used to electronically decouple graphene layers from the SiC substrate, , and subsequently, it was found to be a very effective way to control the electronic properties of the resulting graphene-based heterostructures. …”
Section: Introductionmentioning
confidence: 99%
“…In the slab models, the SiC substrate is represented by six layers of SiC passivated by hydrogen atoms, while in the Green’s function approach, the SiC substrate is represented as a semi-infinite substrate. Although the polar Ga layers are covered by graphene overlayers in the experiment, these graphene layers do not have a significant impact on the low-frequency phonon modes or the interband optical transitions in the energy range of interest here ,, and are not included in the theoretical models.…”
Section: Methodsmentioning
confidence: 99%